Deconstructing the concept of masculinity in Indonesian public service advertisements - Hasan, Yassar; Nugroho, Catur; Wulan, Roro Retno (PRofesi Humas, 2025)
Background: The reason for this research is the rise of hate speech attributed to the rigid concept of traditional masculinity, which leads to toxic masculinity. In addition, there are limited Public Service Advertisements in Indonesia that discuss biased concepts of masculinity. Therefore, public service advertisements on sexual harassment and masculinity produced by Indonesian government agencies, the Indonesian Ministry of Education and Culture, such as “#GerakBersama – Ini Gak Lucu” are interesting to analyze further. Purpose: This study examined how masculinity is represented and the message conveyed in the public service advertisement “#GerakBersama – Ini Gak Lucu”. Methods: To see the representation of masculinity and the message, the public service advertisement was divided into several scenes analyzed using Roland Barthes’ semiotics based on primary and secondary meanings. Results: The study found that the public service advertisement “#GerakBersama - Ini Gak Lucu” is intended to introduce a new concept of masculinity, that a man can still embody masculinity even when performing a beautiful and gentle dance. Conclusion: In this public advertisement, masculinity is also portrayed as men who dare to speak up, demonstrate loyalty, and support one another. Implications: Further research is required to assess the advertisement’s effectiveness in reshaping the social perception of masculinity in Indonesian, specifically whether they hold the traditional perception of masculinity or embrace this new perspective.